Determination of Cd, Cu, Ni and Pb in Selected rice Grain Available in Malaysia - Abd Rashid, R.; A. Muda, N.; Saaid, M.; I. Abdul Halim, M.; Mohamed, K. (International Journal of Engineering and Technology, 2019)
This study aims to determine the levels of heavy metals (cadmium, copper, nickel and lead) in imported and domestically produced rice grains sold in Malaysia market. A total of 10 brands of rice samples was purchased from the local market and analyzed using atomic absorption spectroscopy (AAS). Good linearity was observed over the range studied with a correlation coefficients (R2) of 0.9884-0.9999. The range values of the metals detected in rice grain samples were 0.67-0.8 mg/kg for cadmium, 2.14-7.0 mg/kg for copper, 1.85-2.68 mg/kg for nickel and 0.94-3.28 mg/kg for lead. The mean value of rice obtained were above the permitted level set by the Malaysia Food Act 1983 (Act 281) and Food and Agriculture Organization of the United Nations/ World Health Organization (FAO/WHO) (2015). The Provisional Tolerance Weekly Intake (PTWI) calculated were also above the prescribed limit except for copper.Â Â Â